Sustainable Investment Approaches Enhancing the Decentralization of Corporate Governance across Worldwide Communities - Hiroshige Tanaka; Chiharu Tanaka (Contemporary Research in Business, Management and Economics Vol. 6, 2024)
The manuscript delves into sustainable investment approaches enhancing the decentralization of corporate governance across worldwide communities. The worldwide network of economies and societies is still growing as a result of the digital industrial revolution. However, challenges related to sustainability, like disruption and climate change, have gotten worse. The involvement of multiple stakeholders is essential in addressing challenges related to sustainability in international communities. It is anticipated that multi-stakeholder cooperative and competitive schemes will be used to build sustainable communities. Sustainable global communities must reform centralized economies with top-down systems and must move toward decentralized mechanisms known as bottom-up societies. Sustainable investment strategies to support the environment, society and governance (ESG) presumably improve social welfare. This article describes that multi-stakeholders can introduce a decentralized incentive scheme into global economies and can provide mathematical expressions of sustainable investment strategies. The decentralized formulation described herein is used to evaluate the improvement of ESG initiatives by the decrease of social welfare losses. The formulation states mathematically relative relations among the investment strategies. This mathematical model explores the social welfare effects of initiatives to enhance standards, regulations, and legislation. Empirically, one finds that integration strategies have grown remarkably as a core part of social institutional reform for sustainability. It has been concluded that efforts to enhance social evaluation by those left out of market transactions significantly reduce losses to social welfare. These results may encourage efforts to lessen the disruption challenges that local communities encounter. The results presented herein are expected to be applicable for various global crises. Initiatives by which ESG can solve global crises consistently will be pursued in further research in this field.